Female subjects in black and white: Race, psychoanalysis, feminism - Abel, Elizabeth; Christian, Barbara; Moglen, Helene (University of California Press, 1997)
This landmark collaboration between African American and white feminists goes to the heart of problems that have troubled feminist thinking for decades. Putting the racial dynamics of feminist interpretation center stage, these essays question such issues as the primacy of sexual difference, the universal nature of psychoanalytic categories, and the role of race in the formation of identity. They offer new ways of approaching African American texts and reframe our thinking about the contexts, discourses, and traditions of the American cultural landscape. Calling for the racialization of whiteness and claiming that psychoanalytic theory should make room for competing discourses of spirituality and diasporic consciousness, these essays give shape to the many stubborn incompatibilities―as well as the transformative possibilities―between white feminist and African American cultural formations. Bringing into conversation a range of psychoanalytic, feminist, and African-derived spiritual perspectives, these essays enact an inclusive politics of reading. Often explosive and always provocative, Female Subjects in Black and White models a new cross-racial feminism.
Keywords: afro-féminisme; amériques; approches et analyses; cours; discipline; fem1000; femmes* afro-américaines; féminismes noirs; littérature; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences humaines; états-unis; études littéraires

Gender, ‘Race’, Ethnicity in Art Practice in Post-Apartheid South Africa: Annie E. Coombes and Penny Siopis in Conversation * - Coombes, Annie E. (Feminist Review, 1997)
Siopis has always engaged in a critical and controversial way with the concepts of ‘race’ and ‘ethnicity’ in South Africa. For politically sensitive artists whose work has involved confronting the injustices of apartheid, the current post-apartheid situation has forced a reassessment of their practice and the terms on which they might engage with the fundamental changes which are now affecting all of South African society. Where mythologies of race and ethnicity have been strategically foregrounded in the art of any engaged artist, to the exclusion of many other concerns, the demise of apartheid offers the possibility of exploring other dimensions of lived experience in South Africa. For feminists, this is potentially a very positive moment when questions of gender – so long subordinated to the structural issue of ‘race’ under apartheid – can now be explored. Penny Siopis’ work has long been concerned with the lived and historical relations between black and white women in South Africa. The discussion focuses on the ambivalent and dependent relationships formed between white middle-class women and black domestic labour during apartheid. Siopis’ work engages with how the appropriation of black women's time, lives, labour and bodies has shaped her ‘own’ history.
Keywords: afrique; afrique du sud; antiracisme; apartheid; approches et analyses; arts; cours; discipline; droit des femmes*; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Cultural politics, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Fields of play: Constructing an academic life - Richardson, Laurel W. (Rutgers University Press, 1997)
Comment les circonstances spécifiques dans lesquelles nous écrivons affectent-elles ce que nous écrivons ? Comment ce que nous écrivons affecte-t-il ce que nous devenons ? Comment pouvons-nous maintenir l'intégrité professionnelle et personnelle dans l'université d'aujourd'hui ? Dans une série d'écrits traditionnels et expérimentaux, aboutissement de dix années de travaux en cours, Laurel Richardson enregistre un parcours intellectuel, déplaçant les frontières et créant de nouvelles façons de lire et d'écrire. Appliquant l'imaginaire sociologique au processus d'écriture, elle relie sa vie à son travail. Profondément engageant, écrit de manière émouvante avec grâce, élégance et clarté, le livre stimule les lecteurs à situer leur propre écriture dans des contextes personnels, sociaux et politiques.
Keywords: 1900-1999; 1990-1999; amériques; arts; cours; discipline; fem1000; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; théories féministes; écriture des femmes*; états-unis; études littéraires

Contre-voix : essais de critique au féminin - Saint-Martin, Lori (Collection Essais critiques, 1997)
Keywords: 1900-1999; 1990-1999; amériques; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; lit2815; lit3220; lit3495; littérature; premier cycle; périodes historiques; québec; régions géographiques; thématiques; théories féministes; écriture des femmes*; études littéraires

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Feminisms: An anthology of literary theory and criticism - Warhol, Robyn R.; Price Herndl, Diane (Rutgers University Press, 1997)
This volume brings together 58 previously published essays on 19th and 20th century British and North American texts that were written from the mid-1970s to 1990 by feminist literary critics. These essays cover a variety of critical perspectives, including Anglo-American, French, Marxist, structuralist, new historicist, and psychoanalytic. The 13 sections of the book cover various issues in feminist criticism: institutions, methodologies, canon, tradition, body, desire, reading, discourse, ethnicity, history, class, men, and autobiography. Each section includes essays addressing the intersections of feminist concern with questions of class, race, sexual preference, and nationality. Contributors include Barbara Christian, Sandra M. Gilbert, Susan Gubar, Helene Cixous, and Elaine Showalter
Keywords: 1900-1999; amériques; anthologie; arts; cours; cycles supérieurs; discipline; europe; fem1000; fem7000; histoire et politique; lit3220; littérature; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques; théories féministes; états-unis; études littéraires